Incidence Factors of Negative Environmental Behavior towards the Swamps of Bañó and Los Negros - Jorge Villadiego-Lorduy; Dennis Paul Huffman-Schwocho; Stalyn Yasid Guerrero-Gómez; Adolfo Cortecero-Bossio; Sandra Rivero-Espitia (Universidad Nacional, Costa Rica, 2015)
The purpose of this article is to determine the factors that are influencing the environmentally negative behavior of the inhabitants of Bañó and Los Negros towards these wetlands. For this, a questionnaire was designed, validated by a panel of experts, and implemented. Based on a population of 645 households, we used two types of sample designs -systematic and random- to implement the research instrument. In addition to their respective statistical analysis, a content analysis was carried out with the secondary information collected using index cards. Factors such as low education, scarce employment opportunities, and low income per household have a direct impact on the deterioration of these wetlands. Almost 50% of the population living in the wetlands has not completed basic education. Thus, the possibilities to reflect on the actions done by people against the water mirrors are poor, especially when family incomes are very low (53% of the families receive incomes of less than COL$ 10,000 a day). The scarce organization of the communities has prejudiced the development of joint activities between the neighboring communities of the wetlands, as well as the achievement of common goals. Furthermore, the ineffectiveness of local and national environmental authorities has contributed to the degradation of ecosystems due to an inefficient environmental management over the years. Wetlands are the main source of natural resources for these people and the permanence of such communities in the territory is directly related to the wetlands' conservation. The synergy of the above factors has unleashed environmental problems that have resulted in the reduction of the ecological capacity of these wetlands and the deterioration of environmental conditions in the area of study.